(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article highlights the main points of the outbreak and spread of coronavirus in the world and in Uzbekistan. The analytical conclusions of WHO, a number of scientists about the problems faced by countries, both developed and developing, when faced with the terrible infection of COVID-19, as well as WHO recommendations for combating this infection are presented.